Post‐acute sequelae of COVID‐19 in cancer patients: Two cohorts in UK and Hong Kong - Eric Yuk Fai Wan; Shing Fung Lee; Jiayi Zhou; Vincent Ka Chun Yan; Francisco Tsz Tsun Lai; Celine Sze Ling Chui; Xue Li; Carlos King Ho Wong; Esther Wai Yin Chan; Ian Chi Kei Wong (Cancer Medicine)
Abstract Background Limited research exists on the risks and spectrum of complications in post‐acute phase of COVID‐19 in cancer patients. This study aimed to evaluate the post‐acute effects of COVID‐19 on different types of morbidities among cancer patients across two regions with different healthcare systems and dominant variants of COVID‐19. Materials and Methods Cancer patients with COVID‐19 from the UK Biobank (UKB, n = 2230; March 16, 2020 to May 31, 2021; pre‐Omicron‐variants dominant) and electronic medical records in Hong Kong (HK cohort, n = 22,335; April 1, 2020 to October 31, 2022; Omicron‐variant dominant) were included. Each COVID‐19 case was randomly matched with up to 10 non‐COVID‐19 cancer patients based on age and sex. Follow‐up lasted until 31 August 2021 for UKB and 23 January 2023 for HK. Inverse probability treatment weighting balanced cohort characteristics. Cox regression evaluated the association of COVID‐19 with morbidities occurred 30 days post‐infection. Results Cancer patients with COVID‐19 consistently showed significantly higher risk of major cardiovascular diseases (CVDs) [UKB: hazard ratio [HR] 1.8 (95% CI 1.3, 2.5); HK: HR 1.4 (95% CI 1.1, 1.8)], CVD death [UKB: HR 4.3 (95% CI 2.9, 6.2); HK: HR 1.7 (95% CI 1.3, 2.4)], and all‐cause mortality [UKB: HR 4.7 (95% CI 4.0, 5.5); HK: HR 1.6 (95% CI 1.5, 1.7)] in both cohorts despite the difference in dominant variants. Cancer patients at advanced ages or severely infected had higher all‐cause mortality risk. However, associations between COVID‐19 and CVDs became insignificant for fully vaccinated patients. Conclusion COVID‐19 infection is associated with increased risks of CVDs and mortality in cancer patients. Fully vaccination may reduce the post‐acute effects of COVID‐19 on CVDs. This information may guide effective pre‐emptive measures to reduce COVID‐19‐related morbidities and mortality in cancer patients.